2022
DOI: 10.1108/ijse-12-2021-0732
|View full text |Cite
|
Sign up to set email alerts
|

Impact of institutional quality and human capital creation on economic growth in Bangladesh: evidence from an ARDL approach

Abstract: PurposeThis study examines the impact of institutional quality (INQ) and human capital creation (HCC) on economic growth (EG) linkage in Bangladesh using an ARDL approach.Design/methodology/approachThis study uses time-series annual data over the period 1990–2019. It formulates an INQ index based on international country risk guide (ICRG) data, employs public education outlay and expenditure on health data each as a portion of real gross domestic product (GDP) to measure HCC, while an increase in real GDP is u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 46 publications
1
3
0
Order By: Relevance
“…Similarly, Nawaz (2015) and Şaşmaz and Sağdiç (2020) discovered a positive correlation between institutions and economic growth. Islam and Shindaini (2022) found a similar result in Bangladesh. Recently, Ashraf (2023), using the ARDL bound test, revealed that political stability plays a key role in enhancing economic growth in Pakistan.…”
Section: Introductionsupporting
confidence: 63%
“…Similarly, Nawaz (2015) and Şaşmaz and Sağdiç (2020) discovered a positive correlation between institutions and economic growth. Islam and Shindaini (2022) found a similar result in Bangladesh. Recently, Ashraf (2023), using the ARDL bound test, revealed that political stability plays a key role in enhancing economic growth in Pakistan.…”
Section: Introductionsupporting
confidence: 63%
“…They applied panel data from 1996 to 2019 on 122 developing countries, considered economic and political reforms, and demonstrated that economic reforms were prudential for economic growth, while political reforms remained ineffective to ease economic crises. In a recent study, Islam and Shindaini (2022) used an ARDL framework, examined the effects of INQ and human capital on EG in Bangladesh, and found that INQ stimulated the long-run EG.…”
Section: Literature Reviewmentioning
confidence: 99%
“…At 5% significance levels, a 1% rise in province economic growth reduces the HDI by 11.1% if all other factors remain unchanged. This negative impact of GRDP growth on HDI may partly reflect that economic development may not have been well planned, resulting in a negative impact on human development (Chikalipah and Makina, 2019;Islam and Shindaini, 2022;Li et al, 2023).…”
Section: Static Linear Panel Estimates: Pols Fem and Remmentioning
confidence: 99%